PMSM Rotor Speed and Position Estimator - Said, Mohamed Azmi (2011)
Estimation techniques have been developed for flux observer, rotor position, and speed. The techniques have a common problem of the offset in voltage-sensor and current-sensor outputs increasing during integration, causing instability. This paper describes an attempt to overcome the problem through estimations of rotor position and speed of a permanent magnet synchronous motor (PMSM) by three methods: with cascaded low pass filter (LPF), with adaptive sensorless rotor flux observer, and with sliding mode observer (SMO). Simulation on Matlab/Simulink validated the proposed method. The advantages and drawbacks of each implementation are discussed.